2014
DOI: 10.1371/journal.pone.0091047
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in the Variability and Distribution of Sleep Spindle and Rapid Eye Movement Densities

Abstract: The present study had two main objectives. The first objective was to compare the sleep architecture of young and older adults, with an emphasis on sleep spindle density and REM density. The second objective was to examine two aspects of age differences that have not been considered in previous studies: age differences in the variability of sleep measures as well as the magnitude of age differences in phasic events across the distribution of values (i.e., at each decile rather than a single measure of location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 37 publications
2
23
1
Order By: Relevance
“…The lack of effect on REM density across age is in line with some previous findings (Ficca et al ., ; Peters et al ., ; Vegni et al ., ) and contrary to others (Lauer et al ., ). Future studies may also include additional measures of REMs that not only target the quantity but also the organizational aspects of REM bursts, which according to previous studies are changed in the elderly (Ficca et al ., ; Vegni et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of effect on REM density across age is in line with some previous findings (Ficca et al ., ; Peters et al ., ; Vegni et al ., ) and contrary to others (Lauer et al ., ). Future studies may also include additional measures of REMs that not only target the quantity but also the organizational aspects of REM bursts, which according to previous studies are changed in the elderly (Ficca et al ., ; Vegni et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, K-complexes appear to be linked to delta activity and similarly regulated by homeostatic processes (Halasz, 2005). In contrast to the age-related reduction of spindle and K-complex density, the effect of age on the density of rapid eye movements (REM) is less clear (Lauer et al, 1991;Peters et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth recalling the different age ranges of the training and validation sets and the test set. As observed in [26], the light sleep of young subjects is less than it of senior subjects, while the deep sleep of young subjects is more. Furthermore, the ethnic differences (White in SHHS vs. Asian in our dataset) and gender distributions also lead to dissimilar sleep patterns [27].…”
mentioning
confidence: 83%
“…Given that prior research has demonstrated agerelated declines in sleep spindle characteristics (Nicolas et al 2001;Peters et al 2014), correlations with age were also explored. Consistent with the prior literature, each of the four spindle parameters across all participants was significantly negatively correlated with age (r = À0.46 to À0.66, p < 0.001).…”
Section: Electroencephalographic Analysesmentioning
confidence: 99%